Histidine-Triad Hydrolases Provide Resistance to Peptide-Nucleotide Antibiotics - Eldar Yagmurov (American Society for Microbiology, 2020)
ABSTRACT The Escherichia coli microcin C (McC) and related compounds are potent Trojan horse peptide-nucleotide antibiotics. The peptide part facilitates transport into sensitive cells. Inside the cell, the peptide part is degraded by nonspecific peptidases releasing an aspartamide-adenylate containing a phosphoramide bond. This nonhydrolyzable compound inhibits aspartyl-tRNA synthetase. In addition to the efficient export of McC outside the producing cells, special mechanisms have evolved to avoid self-toxicity caused by the degradation of the peptide part inside the producers. Here, we report that histidine-triad (HIT) hydrolases encoded in biosynthetic clusters of some McC homologs or by standalone genes confer resistance to McC-like compounds by hydrolyzing the phosphoramide bond in toxic aspartamide-adenosine, rendering them inactive. IMPORTANCE Uncovering the mechanisms of resistance is a required step for countering the looming antibiotic resistance crisis. In this communication, we show how universally conserved histidine-triad hydrolases provide resistance to microcin C, a potent inhibitor of bacterial protein synthesis.